2015
DOI: 10.1080/08998280.2015.11929274
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Acute Coronary Syndrome (Kounis Syndrome)

Abstract: Anaphylaxis rarely manifests as a vasospastic acute coronary syndrome with or without the presence of underlying coronary artery disease. The variability in the underlying pathogenesis produces a wide clinical spectrum of this syndrome. We present three cases of anaphylactic acute coronary syndrome that display different clinical variants of this phenomenon. The main pathophysiological mechanism of the allergic anginal syndromes is the inflammatory mediators released during a hypersensitivity reaction triggere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 9 publications
1
32
0
Order By: Relevance
“…Tajda Keber et al [9] suggested measuring cardiac enzymes in acute allergic reaction patients as necessary to diagnose Kounis syndrome promptly and manage cardiac injury early and appropriately. Echocardiography and coronary angiography can provide detailed information to rule out takotsubo cardiomyopathy or other cardiac disorders in cardiac wall motion abnormalities patients [10]. Keita Goto et al [11] reported that thallium-201 (Tl) single-photon emission CT (SPECT) and 125I-15-(p-iodophenyl)-3-(R,S)-methylpentadecanoic acid (BMIPP) SPECT were conducted in a post-Kounis syndrome patient, and they revealed a local perfusion defect with decreased BMIPP uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Tajda Keber et al [9] suggested measuring cardiac enzymes in acute allergic reaction patients as necessary to diagnose Kounis syndrome promptly and manage cardiac injury early and appropriately. Echocardiography and coronary angiography can provide detailed information to rule out takotsubo cardiomyopathy or other cardiac disorders in cardiac wall motion abnormalities patients [10]. Keita Goto et al [11] reported that thallium-201 (Tl) single-photon emission CT (SPECT) and 125I-15-(p-iodophenyl)-3-(R,S)-methylpentadecanoic acid (BMIPP) SPECT were conducted in a post-Kounis syndrome patient, and they revealed a local perfusion defect with decreased BMIPP uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Epinephrine, which is used routinely for the treatment of anaphylaxis, should also be cautiously used, because it may potentially worsen coronary vasospasm and aggravate coronary ischemia in KS. 12 ORCID…”
Section: Discussionmentioning
confidence: 99%
“…The exact role of allergy in cardiovascular disease is not clear and needs more investigations. Some studies have shown the role of allergy and allergic acute coronary syndrome (Kounis syndrome) in patients with ischemic heart disease [20,21]. Recently a population-based, matched cohort study showed that patients with previously diagnosed allergic rhinitis had significantly lower risk for myocardial infarction (P < 0.001) [22].…”
Section: Discussionmentioning
confidence: 99%